Phenolic composition and antioxidant properties of koose, a deep-fat fried cowpea cake. (15th December 2017) - Apea-Bah, Franklin B.; Serem, June C.; Bester, Megan J.; Duodu, Kwaku G.
Highlights: Deep frying of cowpea decreases phenolic content and radical scavenging capacity. Koose contains dietary phenolic compounds that exhibit antioxidant properties. Phenolic compounds in koose protect cells and DNA from oxidative damage. Koose from darker cowpeas exhibit better antioxidant properties than lighter ones. Abstract: Koose, a West African delicacy, is a side dish prepared by deep frying thick cowpea paste. The current research determined the effect of deep-fat frying of cowpea paste on its total phenolic content (TPC), phenolic composition and antioxidant properties. Four cowpea cultivars comprising two reddish-brown, a brownish-cream and cream phenotypes were used. Liquid chromatography-mass spectrometry was used to determine phenolic composition of the samples. TPC was determined using Folin-Ciocalteu method while radical scavenging capacities were by Trolox equivalent antioxidant capacity, oxygen radical absorbance capacity and nitric oxide scavenging assays. The phenolic acids identified included benzoic and cinnamic acid derivatives. The predominant flavonoid classes were flavan-3-ols and flavonols. Deep-fat frying of the cowpea pastes decreased their TPC, radical scavenging capacities and total quantified flavonoids. The koose inhibited radical-induced oxidative cellular and DNA damage. It is concluded that koose is a potential functional food that can contribute to alleviating radical-induced oxidative stress.